DAMPAK GEME ONLINE TERHADAP PERUBAHAN PERILAKU SOSIAL KEAGAMAAN - Arrosikh; Akhmad Khudori (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
This study aims to determine the impact of online games on changes in adolescent behaviour. Data collection was carried out through interviews, documentation and observation. Data analysis is done through the reduction stages, presentation, and conclusion. The study's results showed that the duration of online gameplay reduces adolescent social interaction. In general, it has positive and negative impacts. Positive impacts can improve concentration and language skills and build team solidarity. However, the negative impacts are eye fatigue, aggressive and emotional, and often dishonest.